ANALISA DAN EVALUASI PERHITUNGAN PAJAK PENGHASILAN (PPh) 21 ATAS PENGHASILAN PEGAWAI TETAP SESUAI DENGAN PMK NO. 122/PMK010/2015 (Studi Kasus PT Angkasa Pura I (Persero) Bandara Adisutjipto Yogyakarta) - Rossi Virgajati Septiarini (JURNAL EKOBIS DEWANTARA, 2018)
The aim of this research was to know whether the calculation of Income Tax-Article 21 of PT Angkasa Pura I (Persero) Adisutjipto Airport in a year had referred to Minister of Finance Regulation No. 122/PMK.010/2015.The type of research conducterd was case study. The collection techniques were interview and observation. The steps used were by recalculating Income Tax-Article 21 based on Taxation Rule and compared that result with the calculation of Income Tax-Article 21 from PT Angkasa Pura I (Persero) Adisutjipto Airport. From analysys result showed that calculation process of Income Tax-Article 21 had not referred yet to prevailing Taxation rule implemented in Indonesia. PT Angkasa Pura I (Persero) Adisutjipto Airport had not calculated non taxable income (PTKP) based on Minister of Finance Regulation No. 122/PMK.010/2015, the calculation result of tax system had not refeffed to Minister of Finance Regulation No. 122/PMK.010/2015 and PER-32/PJ/2015 article 10 paragraph (3) a and the calculated of pension contributed had not referred to Government Regulation RI No. 45 2015.